KREOLIZATSIYALASHGAN MATNLARNING BOSMA VA RAQAMLI OMMAVIY AXBOROT VOSITALARIDAGI KORPUSGA ASOSLANGAN QIYOSIY TAHLILI: FUNKSIONAL-PRAGMATIK TA'SIRLAR - Raximjonov Doniyor Shuxratilla o‘g‘li,; Nurbek Gulimmatov Murodboyevich, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Background: While the theory of multimodality is well-established, empirical corpus-based evaluations comparing text creolization across different media landscapes are rare. Objective: This study presents a comparative analysis of creolized texts across print and digital media, evaluating their structural distributions and functional-pragmatic effects on audiences. Methods: Two representative corpora were compiled: a Print Corpus (N = 200) from leading magazines and a Digital Corpus (N = 300) from major multimedia and social media platforms. Qualitative semiotic coding and quantitative pattern analyses were performed. Results: Visual components dominate across both media, appearing in 65% of print ads and over 70% of digital ads. Print media relies heavily on static visual-verbal harmony and verbal anchoring (85%). Digital media utilizes dynamic relay mechanisms, temporal layering, and user-participatory elements. Conclusion: Text creolization is highly adaptive, shaped by media affordances. Print maximizes static layout hierarchy, while digital environments shift communication toward immersive, user-centered multimodal experiences.
Keywords: Keywords: Corpus Analysis, Print Media, Digital Media, Multimodal Discourse Analysis, Functional- Pragmatic Effects, Relay Mechanism.